THE CULTURAL BACKGROUND OF METAPHOR UMPASA IN BATAKNESE WEDDING - Nurkiah Sinaga; Indah Arvianti (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
Language is a means of communication. As a human, we can’t make a communication without languages in our life. There are so many languages in the world; so that it is difficult to understand another language. Language is one of the cultural elements that its role is very important as a means of communication to convey the purpose and subject matter as well as the human mind expresses itself in the social interaction and social life. When we know a language, we can speak and be understood by others who know that language. To understand our humanity we must understand the language that makes us human. Anthropological linguistics is part of linguistics that discusses about the language and its relevancy with culture around the language. In this thesis, the writer will discuss about umpasa Bataknese (kinds of poem in Bataknese) in wedding party. In this umpasa, we will find some metaphors and its culture behind the metaphors. Metaphor is a part of anthropological linguistics that discusses about the real semantically meaning of sentences based on the background culture. In method, the writer uses some strategies; those are collecting the data, analyzing the data and presenting the data. The data collection that is used by the writer is primary and secondary data which are taken from discussion by face to face. The data analysis that is used is metode padan and metode agih. The method of data presentation that is used is informal because the writer will analyze it by using word not by symbol or sign. Bataknese metaphor is influenced by the culture where the metaphor is used. The umpasa Bataknese is a source while the things which they use in wedding process are a target. Here, the writer makes the conclusion that each thing that they use in wedding process has a background culture, which is expressed in umpasa in metaphor. Keywords: Anthropological linguistics, umpasa, metaphor, culture.